PENDIDIKAN MULTIKULTURAL SEBAGAI PENDEKATAN UNTUK MENGURANGI DISKRIMINASI DI SEKOLAH STUDI KASUS DI SD NEGERI KALIANGET - Hasanah, Fitrotul; Milana, Putri; Mubin, Nurul (Cahaya Ilmu Bangsa Institute, 2024)
In schools, multicultural education is an important tool to prevent discrimination that often arises due to differences in ethnicity, religion, race, or culture. Multicultural education is important to be implemented in elementary, middle or high schools in order to foster a sense of mutual respect and tolerance among students. This study aims to determine the approach taken at Kalianget Public Elementary School to reduce discrimination against students. This study uses a qualitative field approach. Data collection techniques with field observations and structured interviews are then analyzed and conclusions are drawn. The results of this study are: Multicultural education provided to students to reduce discrimination in schools include: education about culture, education upholding the values ​​of tolerance, and also humanitarian education. With the multicultural education provided to students, it is hoped that they can become tolerant, inclusive, and anti-discriminatory individuals.